Greenhouse Energy Consumption for Tomato Production in the Iberian Peninsula Countries - Baptista, F.J. (2012)
Greenhouse climate models are a powerful tool which allows the simulation of inside environmental conditions as a function of external conditions, construction and environmental control equipments characteristics. They also permit to evaluate the energy consumption necessary to obtain the predefined conditions. A theoretical study of the greenhouse energy requirements for all year round tomato production in Portugal and Spain is presented. A Greenhouse Climate Simulator (GCS) was used to analyse the energetic behaviour in different regions. GCS uses mensal mean weather data of several years of solar radiation, temperature, wind speed and relative humidity. A climate generator computes the mean hourly climatic data of a typical day for each month and location. As inputs GCS requires data related with the greenhouse characteristics, environmental control equipment and the crop. For the energy balance a static complex model is used which is based on the physics of heat and mass transfer. The results show the energy consumption due to the heating system in each of the studied locations, as well the heat dissipated by the cooling system along a characteristic year, for year round production in plastic greenhouses. This is used to estimate energy consumption indicators which allow generating predictive maps. It is an interesting tool which may contribute to the grower’s decision making and to the reduction of energy consumption, helping to lower production costs and environmental impacts.